Phase of nasal cycle during sleep tends to be associated with sleep stage. (10th April 2013) - Kimura, Akihiro; Chiba, Shintaro; Capasso, Robson; Yagi, Tomoko; Ando, Yuji; Watanabe, Subaru; Moriyama, Hiroshi
<x xml:space="preserve">Abstract</x> Background and Objectives The phenomena of periodic cycles of vascular engorgement on the nasal cavity mucosa that alternate between right and left sides are termed the "nasal cycle." The physiologic mechanisms underlying this cycle have not been entirely clarified, even more so during sleep. In this study, we measured the periodic patterns of the normal nasal cycle, not only during wakefulness but also during sleep. Study Design: Case Series Methods Our team utilized a method for functional rhinologic assessment, the portable rhinoflowmeter (Rhinocycle, Rhinometrics, Lynge, Denmark), measuring airflow independently through each nostril during 24 hours on 20 healthy subjects aged 20 to 56 years, and without any nasal pathology or diagnosed medical, psychiatric, or sleep disorders. In addition, a nocturnal polysomnogram was simultaneously performed during sleep. Results Nineteen of 20 subjects showed a detectable nasal cycle, and 16 of 19 subjects presented a change of the cyclic phase during sleep. The mean nasal cycle duration was 234.2±282.4 minutes (median, 164.1 minutes), although variation was considerable. The mean cycle duration time during sleep was significantly longer than that in wakefulness (P <0.005). The reversal of cyclic phase during sleep tended to be associated with REM sleep (68.8%) and postural changes (18.8%). It never occurred in slow‐wave sleep. Conclusions Nasal cycle duration during sleep is longer than in wakefulness. Changes in laterality of nasal cycle frequently coincide with switches in posture, tend to occur in REM sleep, never occur in slow‐wave sleep, and may be absent in subjects with severe nasal septal deviations. Level of Evidence 4. Laryngoscope, 123:2050–2055, 2013